INCLUSIVE EDUCATION: A LOOK AT HEARING IMPAIRMENT - Pereira de Caldas, Marinez; Dias da Silva, Damiana; Pereira de Queiroz Nunes, Zenilda; Joseny Ferreira da Silva, Maria; de Sá Leite Ferreira Lacerda, Sheila (Revista Gênero e Interdisciplinaridade, 2024)
This article aims to address a topic that is of concern to educators, the inclusion of the hearing impaired and about pedagogical practices that the teacher should be aware of when assisting the hearing impaired student. Much has been debated about inclusion in the educational area and, in this context, the education of the hearing impaired. It is of great importance the teacher’s collaboration in this fight against inequality, but unfortunately not everyone has the necessary knowledge to receive students with this type of disability. It is notorious that teachers are not yet ready to attend the hearing impaired student, the most frequent difficulties are related to communication and to the teaching and learning process. The inclusion has precisely widened the possibilities to build a more just society, giving opportunities for all, to occupy their spaces, seeking to gain their autonomy. Hearing impairment harms not only in language, but also in the educational area, in its potentiality and in its integration into social life. It is necessary for the teacher to value the singularities of each child, in this way the hearing impaired student will have respected their personal characteristics as well as their learning pace. The work presents a bibliographical review, in which it was sought to expand the information regarding the subject studied, demonstrating the process of guaranteeing the rights of the hearing impaired in the legislation. We also sought to discuss with authors about the theme, in order to understand the concept of inclusion.